Note of the Recent Excavation of a Cairn on the High Law, and of other Antiquities in the Parish of Cruden, Aberdeenshire. (with Additional Notes by Stuart, John) (Proceedings of the Society of Antiquaries of Scotland, 1862)
This paper records the excavation of a cairn in Aberdeenshire by Major-General Moore and Mr Alex Murray. The excavators concluded that the cairn and the cist below it had been examined before, based on the looseness of the stones making up both structures. The Major-General was also involved in a dig at St Olaf's Church nearby, where he unearthed some human remains. The article ends with a short exploration of Scandanavian influence in Scotland by the Secretary, John Stuart. A committee was also formed at this meeting to investigate the history and structure of the Scottish language.